Megaherbivores may impact expansion of invasive seagrass in the Caribbean - Christianen, Marjolijn J. A.; Smulders, Fee O. H.; Engel, M. Sabine; Nava, Mabel I.; Willis, Sue; Debrot, Adolphe O.; Palsbøll, Per J.; Vonk, J. Arie; Becking, Leontine E. (The Journal of ecology, 2019)
1. Our knowledge of the functional role of large herbivores is rapidly expanding, and the impact of grazing on species coexistence and nonnative species expansion has been studied across ecosystems. However, experimental data on large grazer impacts on plant invasion in aquatic ecosystems are lacking. 2. Since its introduction in 2002, the seagrass species Halophila stipulacea has rapidly expanded across the Eastern Caribbean, forming dense meadows in green turtle (Chelonia mydas)—foraging areas. We investigate the changes in seagrass species coexistence and the impacts of leaf grazing by green turtles on nonnative seagrass expansion in Lac Bay (Bonaire, Caribbean Netherlands). 3. Green turtle grazing behaviour changed after the introduction of nonnative seagrass to Lac Bay in 2010. Field observations, together with time-lapse satellite images over the last four decades, showed initiation of new grazing patches (65 ha, an increase of 72%). The sharp border between grazed and ungrazed seagrass patches moved in the direction of shallower areas with native seagrass species that had previously (1970-2010) been ungrazed. Green turtles deployed with Fastloc-GPS transmitters confirmed high site fidelity to these newly cropped patches. In addition, cafeteria experiments indicated selective grazing by green turtles on native species. These native seagrass species had significantly higher nutritional values compared to the nonnative species. In parallel, exclosure experiments showed that nonnative seagrass expanded more rapidly in grazed canopies compared to ungrazed canopies. Finally, in 6 years from 2011 to 2017, H. stipulacea underwent a significant expansion, invading 20-49 fixed monitoring locations in Lac Bay, increasing from 6% to 20 % in total occurrence. During the same period, native seagrass Thalassia testudinum occurrence decreased by 33%. 4. Synthesis. Our results provide first-time evidence of large-scale replacement of native seagrasses by rapidly colonizing Halophila stipulacea in the Caribbean and add a mechanistic explanation for this invasiveness. We conclude that green turtle leaf grazing may modify the rate and spatial extent of this invasive species' expansion, due to grazing preferences, and increased space for settlement. This work shows how large herbivores play an important but unrecognized role in species coexistence and plant invasions of aquatic ecosystems.